Kontribusi Instrumen Ekonomi Islam Terhadap Pertumbuhan Ekonomi: Studi Literatur - Ristiyanti Ahmadul Marunta; Nurul hildayani; Umi ulhusna; Muh. Ridwan malik (STIE Amkop Makassar, 2025)
This study aims to analyze the contribution of three main instruments of Islamic economics zakat, waqf, and sukuk—to inclusive and sustainable national economic growth. Using a qualitative literature study approach, this research explores secondary data from various journals and relevant scientific sources. The findings indicate that zakat can increase the purchasing power of low-income communities and accelerate consumption through productive zakat programs. Waqf provides long-term contributions by offering productive social assets such as education and healthcare, which directly enhance the quality of human resources. Meanwhile, sukuk serves as a strategic financing solution for national infrastructure development, driving investment growth and job creation. This study also emphasizes the importance of integrating these three instruments, for example, through sukuk-based productive waqf and the empowerment of zakat recipients in managing waqf assets. Optimal implementation requires institutional synergy, enhanced Islamic financial literacy, and government regulatory support. Thus, zakat, waqf, and sukuk are not merely spiritual financial instruments, but also fundamental pillars of just economic development from an Islamic perspective.